Conservation laws for two-phase filtration models; Communications in Nonlinear Science and Numerical Simulation; Vol. 19, iss. 2 - Baikov V. A. Vitaly; Ibragimov N. Kh. Nail; Zheltova I. S.; Yakovlev A. A. Andrey Alexandrovich (2014, 2014)
Title screen